2021
DOI: 10.1021/acschembio.1c00268
|View full text |Cite
|
Sign up to set email alerts
|

Protected N-Acetyl Muramic Acid Probes Improve Bacterial Peptidoglycan Incorporation via Metabolic Labeling

Abstract: Metabolic glycan probes have emerged as an excellent tool to investigate vital questions in biology. Recently, methodology to incorporate metabolic bacterial glycan probes into the cell wall of a variety of bacterial species has been developed. In order to improve this method, a scalable synthesis of the peptidoglycan precursors is developed here, allowing for access to essential peptidoglycan immunological fragments and cell wall building blocks. The question was asked if masking polar groups of the glycan pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…In the case of the newly developed DH5α-Tf-KU strain, when supplementing with AzNAM, we found that DH5α-Tf-KU was able to recover cell growth at all AzNAM concentrations tested for approximately 3 h and concentrations of 150 μM and above for at least 6 h (Figure A). These conditions are superior to the previous conditions for EQKU cells which could only recover growth with AzNAM at concentrations of 600 μM and above (Figure B) . These data suggest that the AmgK/MurU homologues from T. forsythia are more efficient at utilizing the NAM probes and are therefore better suited for a PG remodeling strategy.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…In the case of the newly developed DH5α-Tf-KU strain, when supplementing with AzNAM, we found that DH5α-Tf-KU was able to recover cell growth at all AzNAM concentrations tested for approximately 3 h and concentrations of 150 μM and above for at least 6 h (Figure A). These conditions are superior to the previous conditions for EQKU cells which could only recover growth with AzNAM at concentrations of 600 μM and above (Figure B) . These data suggest that the AmgK/MurU homologues from T. forsythia are more efficient at utilizing the NAM probes and are therefore better suited for a PG remodeling strategy.…”
mentioning
confidence: 70%
“…These conditions are superior to the previous conditions for EQKU cells which could only recover growth with AzNAM at concentrations of 600 μM and above (Figure 3B). 18 These data suggest that the AmgK/MurU homologues from T. forsythia are more efficient at utilizing the NAM probes and are therefore better suited for a PG remodeling strategy.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…30 μl of DBCO-488 was added to appropriate wells. The plate was incubated at 37°C in the plate reader where it was shaken for 2 min, scanned at 600 nm, and then repeated every 20 min for 6 h ( Brown et al, 2021a ). Cell growth curves were formulated with Origin 2019.…”
Section: Methodsmentioning
confidence: 99%